Variability of the level of development of functional urbanareas - Szafranek, Edyta (Research Papers of Wrocław University of Economics, 2018)
Functional urban areas are of high importance both in the implementation of the National Urban Policy 2023 and territorial development policy. The objective of the study is to determine the level of development of functional areas of voivodship capitals in Poland. The study involved the application of the taxonomic method in a dynamic approach covering the period 2005-2015. The determination of taxonomic values was based on a set of diagnostic indicators in three dimensions of development: social, economic, and environmental. The study involved the assessment of the level of development of central cities of FUA, and separately of cities and the surrounding communes. Moreover, the level of development of each of dimensions of sustainable development was determined. This permitted the assessment of the structure of development of functional areas in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 502, s. 113-124
Keywords: functional urban areas; level of development; sustainable development; growth centres; taxonomic method; miejskie obszary funkcjonalne; poziom rozwoju; rozwój zrównoważony; centra wzrostu; metoda taksonomiczna; wymiar społeczny; gospodarczy; środowiskowy